PENGARUH JENIS PEWARNA PADA PROSES ANODIZING ALUMINIUM T6 6061 TERHADAP HASIL PELAPISAN - Hidayat, syarif; Darmo, Adityo Noor Setyo Hadi; Iswahyudi, Sigit (ELEMEN : JURNAL TEKNIK MESIN, 2025)
This study examines anodizing on aluminum 6061 using chemical dyes (printer ink and clothing dye) and a natural dye (turmeric) at concentrations of 5%, 10%, and 15% w/v. The anodizing process was conducted at 12 volts, 2.5 amps, for 30 minutes. The research aims to evaluate the effects of dye type and concentration on color brightness, oxide layer thickness, and wear rate. Results indicate that dye concentration influences brightness, with the best outcome at 10% w/v printer ink (brightness level 5.4). Oxide layer thickness was unaffected by the type or concentration of dye used. Wear testing revealed that dyeing did not significantly affect wear resistance, with the highest specific wear rate on untreated material (11.01 x 10⁻⁴ mm³/kg.m) and the lowest on 10% w/v printer ink (7.63 x 10⁻⁴ mm³/kg.m). Overall, the findings suggest a limited impact of dye on the anodized aluminum's wear properties.